Which ? guide to women's health - Robinson, Ann (Which ? Ltd LondonGB, 1999)
Addresses key health issues facing women. Identifies factors that determine physical, emotional and mental well-being. Advises on topics including: fertility, pregnancy, menopause, cosmetic surgery, the cardiovascular system, the head and nervous system, and the care of, as well as diseases of the bones and joints.